Eco-City as A Concept of Samarinda City Development After the Relocation of The National Capital - Idris, Ahmad Syahir; Hariadi, Akhmad; Yenita, Yenita; B, Jauchar; Alaydrus, Anwar; Nurmiyati, Niken (Universitas Sultan Ageng Tirtayasa, 2025)
The relocation of the country's capital has had a positive and a negative impact on the city of Samarinda. The eco-city concept was put forward as a solution to this challenge. This research aims to explore the application of eco-city in the construction of Samarinda City. Descriptive analysis and interviews are the methods employed. The results show that eco-cities can boost economic growth while reducing the impact of excessive urbanization. This research is qualitative, using a literary study approach. The study looks at the concept of eco-cities by focusing on indicators of mass transport development, building decent, affordable, and versatile housing, and reducing pollution and waste. The findings of this study indicate that the Samarinda City Government's vision, mission, and regional excellence programs have indirectly adopted the principle of eco-city. However, in terms of implementation, it is still far from the concept of an eco-city itself.